A narrative review evaluating the safety and efficacy of e-cigarettes as a newly marketed smoking cessation tool. (August 2019) - Worku, Dominic; Worku, Elliott
Introduction: E-cigarettes are an alternative to traditional tobacco-based cigarettes. While having considerable societal awareness, conflicting evidence exists to support their claims that they are an effective smoking cessation tool and are safe. Currently >7000 flavours exist with evidence that they exhibit detrimental cellular and tissue effects. A literature review was conducted utilising PubMed and Google Scholar Databases identifying papers between 2014 and 2019. The aims of this study were to accurately gauge the safety and efficacy of e-cigarettes as a smoking cessation tool. Methods: Search terms including 'electronic cigarettes' and 'vaping' were used to identify suitable references. A total of 314 articles were identified from which papers were excluded due to risk of bias, insufficient detail or were duplicate from which 58 papers were used in the final review. Results: Evidence shows that e-cigarettes can have detrimental effects on several cell lines and animal models with their flavourings and nicotine content implicated; this has, however, not translated into major health outcomes after 3.5 years follow-up but has been linked to chronic lung disease and cardiovascular disease. While advertised as an effective smoking cessation tool, no consensus can be made regarding their effectiveness although the first robust randomised controlled trial reports some success. This, however, is offset by the fact that the most common e-cigarette use is as a dual user and that there is evidence of threefold increased risk of future tobacco smoking. Conclusion: Future research is needed to evaluate the long-term health outcomes and efficacy of e-cigarettes as a smoking cessation tool with greater discussion between patients and clinicians regarding this smoking cessation tool.